Whole-body biodistribution and radiation dosimetry of [18F]PR04.MZ: a new PET radiotracer for clinical management of patients with movement disorders - Wencke Lehnert; Patrick J. Riss; Ana Hurtado de Mendoza; Sandra Lopez; Gonzalo Fernandez; Marcelo Ilheu; Horacio Amaral; Vasko Kramer (EJNMMI Research, 2022)
Abstract Purpose [18F]PR04.MZ is a new PET imaging agent for dopamine transporters, providing excellent image quality and allowing for the evaluation of patients with movement disorders such as Parkinson’s disease. The objective of this study was to evaluate the biodistribution and radiation dosimetry of [18F]PR04.MZ by serial PET imaging. Methods Six healthy subjects (n = 3 males, n = 3 females) were enrolled in this study. A series of 14 whole-body PET/CT scans were acquired until 5.5 h post-injection of 200 ± 11 MBq of [18F]PR04.MZ. After rigid co-registration, volumes of interest were outlined either on CT or PET images. Time-integrated activity coefficients were calculated for selected source organs. Organ absorbed doses, and the effective dose were calculated using IDAC-Dose 2.1. Results Physiological uptake of [18F]PR04.MZ was mainly observed in the striatum, brain, liver, gall bladder, intestine, red marrow and cortical bone. [18F]PR04.MZ was primarily excreted via hepatobiliary clearance and, to a lower extent, via renal clearance. The normalized absorbed doses were highest in gall bladder wall (32.2 ± 6.4 µGy/MBq), urinary bladder wall (27.2 ± 4.5 µGy/MBq), red marrow (26.5 ± 1.4 µGy/MBq), cortical bone surface (26.3 ± 2.5 µGy/MBq), liver (22.5 ± 1.8 µGy/MBq) and kidneys (21.8 ± 1.1 µGy/MBq). The effective dose according to ICRP 60 and 103 was 16.3 ± 1.1 and 16.6 ± 1.5 µSv/MBq, respectively. Conclusion [18F]PR04.MZ has a favourable dosimetry profile, comparable to those of other 18F-labelled PET tracers, and is suitable for larger clinical applications. Trial registration CEC SSM Oriente, Santiago, Chile, permit 20140520.